2017
DOI: 10.1016/j.ijcard.2017.01.153
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of frailty in heart failure: A systematic review and meta-analysis

Abstract: Background There is a growing interest in the intersection of heart failure (HF) and frailty; however, estimates of the prevalence of frailty in HF vary widely. The purpose of this paper was to quantitatively synthesize published literature on the prevalence of frailty in HF and to examine the relationship between study characteristics (i.e. age and functional class) and the prevalence of frailty in HF. Methods The prevalence of frailty in HF, divided into Physical Frailty and Multidimensional Frailty measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
226
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(281 citation statements)
references
References 53 publications
13
226
2
7
Order By: Relevance
“…Thirdly, we do not have details on the clinical presentation, ejection fraction or natriuretic peptide levels in these patients so cannot comment on severity of HF or differences in admission thresholds for frail versus nonfrail patients. Interestingly, a systematic review of 26 studies (6896 patients) reported no association between HF class and prevalence of frailty . Fourthly, we cannot conclusively state the underlying reasons for the observed associations and the possibility of unrecognized residual confounding exists in any observational study.…”
Section: Discussionmentioning
confidence: 84%
“…Thirdly, we do not have details on the clinical presentation, ejection fraction or natriuretic peptide levels in these patients so cannot comment on severity of HF or differences in admission thresholds for frail versus nonfrail patients. Interestingly, a systematic review of 26 studies (6896 patients) reported no association between HF class and prevalence of frailty . Fourthly, we cannot conclusively state the underlying reasons for the observed associations and the possibility of unrecognized residual confounding exists in any observational study.…”
Section: Discussionmentioning
confidence: 84%
“…The relation between the New York Heart Association functional class and the prevalence of frailty is not clear as some studies found a poor association while others a linear correlation . This can be probably related to the methods used for the assessment of frailty.…”
Section: Frailty In Heart Failurementioning
confidence: 99%
“…Frailty is more prevalent in HF than the general population. The estimated overall prevalence of frailty in HF is around 45%, with a lower prevalence in studies using the physical frailty assessment tool compared to those using the cumulative deficit approach (42.9% vs. 47.4%) . Patients with HF are up to six times more likely to be frail, and frail people have a significantly increased risk of developing HF …”
Section: Frailty In Heart Failurementioning
confidence: 99%
“…Frailty has been measured using a number of different instruments in clinical trials and observational studies . The approach used to conceptualize frailty generally falls into two groups: frailty defined by phenotype (sometimes termed physical frailty) and frailty defined by a deficit accumulation approach (sometimes termed multi‐dimensional frailty) .…”
Section: Introductionmentioning
confidence: 99%